Imagens espectrais do processo de agregação da insulina por complexos metálicos luminescentes - Pereira, Lorena Maria Borges (2021)
Insulin is a protein hormone synthesized by β cells in the pancreas, which regulates the level of glucose in the blood. This protein was the first biopharmaceutical produced on an industrial scale for the treatment of diabetic patients. However, the formation of amyloid insulin aggregates is one of the most common and problematic processes found during the production, storage and distribution of drugs based on this hormone, since this process reduces the effectiveness of drugs and, consequently, limits treatment of diabetic patients. The present work aims to monitor in vitro the process of aggregation of bovine insulin using the cis- [Ru (phen)2(3,4-Apy) 2]2+ complex as a luminescent probe. The complex has an intense absorption band in the ultraviolet region (λmax = 260 nm, ε = 70 200 mol-1.L.cm-1) typical of the transitions of unsaturated aromatic ligands (ILCT) and a wide absorption band in the region visible (λmax = 440 nm, ε = 9 650 mol-1.L.cm-1) attributed to the charge transfer transition from metal to ligand (MLCT, Ru, dπ → phen, π*). The complex has a maximum emission at 655 nm, after being excited at 480 nm, an emission lifetime (em) of 60.88 and 0.594 ns in phosphate buffer pH 7.0, with a Stokes shift of around 4 800 cm-1. These spectroscopic properties indicate the potential of this complex for application as a luminescent probe in a biological environment. The insulin aggregation process was investigated as a function of the incubation time, in the absence and presence of the cis-[Ru(phen)2(3,4-Apy)2]2+ complex. From the luminescence assays it was possible to observe that the complex can monitor the insulin aggregation kinetics. The limit for insulin fiber detection was 0.85 M. This low detection limit value indicates that the complex is efficient in detecting amyloid species. The interaction affinity of the complex with the amyloid fibrils was evaluated through the dissociation constant (Kd), the calculated Kd value corresponds to 13.50 ± 1.84 M. The stoichiometry of the ligand between complex and fibers was determined as 1 complex: 2 insulin fibers. Fluorescence microscopy images indicate that it can act as an amyloid marker. Based on these results, it can be concluded that the complex can act as an amyloid marker in the insulin aggregation process.